2022
DOI: 10.21053/ceo.2022.01004
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Viruses in the Inception of Chronic Rhinosinusitis

Abstract: Chronic rhinosinusitis (CRS) is a complex inflammatory disorder that affects between 2 and 16% of adults in the United States with estimated healthcare costs between 4 to 12 million USD. Viruses are a frequent cause of upper respiratory infections and a trigger for CRS exacerbations. There are several cross-sectional studies that have identified types of viruses associated with CRS. Rhinovirus, parainfluenza virus, influenza virus, and respiratory syncytial virus were the main associated viruses found in nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Indeed, the PIV receptor CX3CR1 colocalizes to motile cilia is a plausible viral entry mechanism into the cells [62]. An additional study showed that the intercellular adhesion molecule-1 (ICAM-1) and related cytokine molecules is induced by PIV3 and it is thought that this activation participates in the inflammation during infection by viruses [63,64] (Figure 1A). Further research using the powerful of the transcriptomic analysis is necessary to help to delineate the role of PIV and implicated mechanisms in the development of the broad range of olfactory dysfunctions in patients and to find host-response transcript signature for possible treatments.…”
Section: Viruses Impacting Respiratory Systemmentioning
confidence: 97%
“…Indeed, the PIV receptor CX3CR1 colocalizes to motile cilia is a plausible viral entry mechanism into the cells [62]. An additional study showed that the intercellular adhesion molecule-1 (ICAM-1) and related cytokine molecules is induced by PIV3 and it is thought that this activation participates in the inflammation during infection by viruses [63,64] (Figure 1A). Further research using the powerful of the transcriptomic analysis is necessary to help to delineate the role of PIV and implicated mechanisms in the development of the broad range of olfactory dysfunctions in patients and to find host-response transcript signature for possible treatments.…”
Section: Viruses Impacting Respiratory Systemmentioning
confidence: 97%
“…Indeed, the PIV receptor CX3CR1 colocalizes to motile cilia and is a plausible viral entry mechanism into the cells [ 55 ]. An additional study showed that the intercellular adhesion molecule-1 (ICAM-1) and related cytokine molecules are induced by PIV3, and it is thought that this activation participates in the inflammation during infection by viruses [ 56 , 57 ] ( Figure 1 ). Further research using the power of the transcriptomic analysis is necessary to help delineate the role of the PIV and implicated mechanisms in the development of the broad range of olfactory dysfunctions in patients and to find host-response transcript signatures for possible treatments.…”
Section: Viruses Impacting Respiratory Systemmentioning
confidence: 99%
“…As a PIV, the RSV targets the cilia of the epithelial cells in the airways by fusionning its F-glycoprotein to the cellular receptor human nucleolin (NCL). RSV also uses another mechanism that activates protein kinases like IGF1R to get into the cells [ 56 , 68 , 69 ]. Furthermore, recent studies have shown the essential role of the nucleolin RNA binding domain RBD1,2 in allowing the infection of RSV [ 70 ].…”
Section: Viruses Impacting Respiratory Systemmentioning
confidence: 99%
“…Similar results were uncovered in AECs, where HRV infection decreased TJ expression at the epithelial barrier, reduced epithelial TER, and dissociated ZO-1 from TJ [ 187 , 188 , 189 ]. HRV can disrupt epithelial barrier function, and provide an environment for subsequent allergens to cross the epithelial cell layer and secondary responses [ 190 ].…”
Section: Risk Factors Contributing To Epithelial Barrier Disruptionmentioning
confidence: 99%